2017
DOI: 10.1016/j.envint.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between gaseous air pollutants and inflammatory, hemostatic and lipid markers in a cohort of midlife women

Abstract: BACKGROUND Exposures to ambient gaseous pollutants have been linked to cardiovascular diseases (CVDs), but the biological mechanisms remain uncertain. OBJECTIVES This study examined the changes in CVD marker levels resulting from elevated exposure to ambient gaseous pollutants in midlife women. METHODS Annual repeated measurements of several inflammatory, hemostatic and lipid makers were obtained from 2,306 midlife women enrolled in the longitudinal Study of Women’s Health Across the Nation (SWAN) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 56 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Our previous studies have found that one-year exposures to PM 2.5 , NO 2 , and CO were positively associated with PAI-1 [ 18 , 19 ]. In two-pollutant models along with PM 10–2.5 , PM 2.5 , CO, and NO 2 were each still positively associated with PAI-1 levels, and the associations were stronger for PM 2.5 , CO, and NO 2 than PM 10–2.5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have found that one-year exposures to PM 2.5 , NO 2 , and CO were positively associated with PAI-1 [ 18 , 19 ]. In two-pollutant models along with PM 10–2.5 , PM 2.5 , CO, and NO 2 were each still positively associated with PAI-1 levels, and the associations were stronger for PM 2.5 , CO, and NO 2 than PM 10–2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…Site was included as a fixed effect because participants were nested within each site. First-order ante-dependence structure was specified for repeated measurements from each participant [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentration of ambient CO is considered too low to induce the toxic effects of CO [ 51 ]. Several plausible biological mechanisms underlying the association between low concentrations of ambient CO with CVD have been proposed, including cardiac dysfunction [ 52 , 53 ], systemic inflammation [ 54 , 55 ], oxidative stress [ 56 , 57 ], and thrombotic reaction [ 55 ]. Both animal models and population-based cohort studies have demonstrated the cardiotoxicity of CO [ 48 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study confirmed that high-sensitivity C-reactive protein increased with short-term exposure to CO among 61 patients with cardiovascular disease [ 55 ]. Fibrinogen and D-dimer significantly also increased with ambient CO exposure, and these biomarkers are related to thrombotic reactions [ 54 , 55 ]. Overall, the scientific evidence supports that ambient CO exposure is associated with cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%